2006
DOI: 10.2135/cropsci2005.08-0270
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Mechanisms Associated with the Effect of Spring Wheat Seed Size on Wild Oat Competition

Abstract: Crop seed size affects the competitive relationship between spring wheat (Triticum aestivum L.) and wild oat (Avena fatua L.). However, the mechanisms associated with the process are not known. The effect of wheat seed size on wild oat competition was assessed by a mechanistic approach involving yield and its determinants in these species. Wheat plants established from large and small seed were evaluated under different seeding rates and wild oat densities during 1999–2001 near Kalispell, MT. Linear structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Ali Abadi et al (2011) reported that germination, seedling dry weight, seedling vigor and seedling length increased by increasing in seed size. Larger seeds develop better root system of seedling and advantage of deep root is to get soil moisture efficiency from deeper layers of soil (Guillen-Portal et al, 2006). Moreover, osmopriming with CaCl2 significantly improved the grain yield of wheat under conventional and zero tillage while improved the straw and grain yield only under conventional tillage system.…”
Section: Discussionmentioning
confidence: 99%
“…Ali Abadi et al (2011) reported that germination, seedling dry weight, seedling vigor and seedling length increased by increasing in seed size. Larger seeds develop better root system of seedling and advantage of deep root is to get soil moisture efficiency from deeper layers of soil (Guillen-Portal et al, 2006). Moreover, osmopriming with CaCl2 significantly improved the grain yield of wheat under conventional and zero tillage while improved the straw and grain yield only under conventional tillage system.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, large vs. small seed size reduced panicle density by 15%, and biomass and seed production by 25% (Xue and Stougaard 2002). Guillen-Portal et al (2006) also determined that competitive ability of spring wheat against A. fatua was enhanced by planting large vs. small seeds.…”
Section: Response To Other Human Manipulationsmentioning
confidence: 89%
“…Blackshaw et al (1981) reported that increasing Setaria veridis density decreased the spikelet number of wheat, floret fertility and grain number per spike through shading effect of weed. Also, Guillen-Portal et al (2006) revealed that the grain number per wheat spike significantly decreased in the presence of wild oat (Avena fatua L.).…”
Section: Number Of Grains Per Spike and 1000 Grain Weightmentioning
confidence: 99%